PENGARUH PENAMBAHAN BERBAGAI LEVEL MAGGOT SEGAR DALAM RANSUM TERHADAP PRODUKSI TELUR ITIK MOJOSARI: THE EFFECT OF ADDING VARIOUS LEVELS OF MAGGOT IN THE RATE ON THE PRODUCTION OF MOJOSARI DUCK EGGS - Ajibarata, M.Fahri Islah; Wulandari, Eudia Christina; Suhardi, Suhardi (Tropical Animal Science, 2023)
Ducks are dual-purpose livestock that produce meat and eggs in Indonesia. Success in raising ducks is in feed consumption, the surrounding environment, the housing system and its genetic potential. The feed rations given must be highly nutritious and support growth. This study used 60 laying ducks, using a completely randomized design (CRD) with 4 treatments consisting of 3 ducks as the treatment was repeated 5 times. The treatments are: T0 =(100% Prepared feed), T1 =(5% Maggot +100% Prepared feed) , T2 =(10% Maggot +100% Prepared feed) and T3 =(15% Maggot +100% Prepared feed) ). Parameters observed were ration consumption, hen day production, egg weight, shell thickness and shell weight. The results showed that treatment had a significant effect (P>0.05) on egg weight T0 (68.9a), T1 (67.02ab) , T2(70.26a ), T3(73.42b ). But it has no significant effect ( P<0.05) on ration consumption T0( 195.94) ,T1( 200.36), T2( 205.39), T3(210.01) Hen day production T0( 84.4%), T1( 82.2%), T2( 98.2%), T3(96.4% ). Shell thickness T0 (0.58), T1(0.58), T2(0.59), T3(0.55) and Shell weight T0( 6.62), T1(6.82), T2(6, 86), T3(7). The conclusion in this study was that laying ducks could consume fresh maggot in increasing egg production with reference to the provision of 10% maggot and it had an effect on egg weight but had no significant effect on ration consumption, HDP, shell thickness and shell weight.